THE INFLUENCE OF SIDE FRICTION ON TRAFFIC ON FATIMA AL-ZAHRA STREET IN KARBALA: CAUSES, RESULTS AND SOLUTIONS - Hayder Salman Khudhair; Vladimir N. Konoplev; Hamid A.E. Al-Jameel (International Journal of Advanced Studies)
Side friction is considered one of the main reasons for reducing the efficiency of traffic in urban streets and is caused by a number of factors, such as parking vehicles on the side of the road, pedestrians crossing in places not intended for them, vehicles entering the main road from secondary roads and leaving it on secondary roads, etc. The scientific novelty of this work lies in the fact that for the first time, as far as we know, it provides a statistical description of the influence of Side friction factors on traffic efficiency on Fatima Al-Zahra Street in Karbala, as well as on the classification of roads. The results of the study showed that side friction is responsible for significantly reducing the operating efficiency of the studied road, as well as reducing the road classification.